Pengaruh Modal, Lokasi, dan Promosi Terhadap Perkembangan Usaha Mikro Kecil dan Menengah (Studi UMKM Bidang Kuliner di Talang Banjar Jambi Timur) - Elga Belfani; Efni Anita; Sri Rahma (CV. Aksara Global Akademia, 2023)
This research aims to find out the influence of capital, location and promotion on business development among UMKM in the culinary sector in Talang Banjar, East Jambi. This research uses a quantitative approach and the data analysis method used is multiple linear regression analysis. The sample used was 100 UMKM actors in the Talang Banjar sub-district. The results of research on capital partially influence business development obtained a value of 2,150 > 1,660 and a significant value of 0.034 < 0.05. Location partially influences business development, with a value of 2,101> 1,660 and a significant value of 0.038 < 0.05. Promotion partially influences business development, with a value of 1,934> 1,660 and a significant value of 0.032 < 0.05. The research results based on the f test show that the calculated f value of 3,695 is greater than the f table of 2,698 or 3,695 > 2,698. So it can be concluded that Ho is rejected and Ha is accepted, which means that there is a significant influence between capital, location and promotion simultaneously or together influencing business development. The Adjusted R Square value is 0.475 or 47.5%. This shows that the business development variable is influenced by capital, location and promotion by 47.5%, while the remaining 52.5% of the business development value is influenced by other variables not included in the research